Design And Analysis Of Frontal Bumper And Crash Box Energy Absorption On Bishoftu Bus - Bulti, Buzuneh (ASTU, 2022)
Bumper Beams Are Shock-Absorbing Parts. They Are Attached To The Front And Rear Ends Of Vehicles By Means Of Brackets, Which Act As Crash Boxes By Taking The Loads Mainly In The Axial Direction. Due To Their Heavy Weight And Speed In The In The City, Accidents Occurred On Bishoftu Bus. Since No Bumper And Crash Box On The Bus It Initiate To Design Energy Absorber. The FocusOf This Thesis Work Is To Design Frontal Bumper Beam And Crash Box For Bishoftu Bus For Improving Energy Absorption During Collision. In This Work Different Models Are Analyzed And Simulated To Study The Effect Of Impact Load On Bumper Beam And Crash Box Located On Front Face Of Bishoftu Bus. Solid works Is Used For Modeling, Ansys Is Used For Analyses And Simulation Of The Impact. Impact Simulation Is Done A Crash Speed Of 30 Km/H, With Mass Of Vehicle As 18000 Kg. The Material Selected Is Pc/0.5 Wt.% Nano Alumina (Nano Composite Foam) For The Intersection Of Bumper And Crash Box. Reverse C Profile (Rcp) Is Used For Geometry. The Bumper Beam And Crash Box On Frontal Face Of The Bus Were Analyzed For Energy Absorption During Impact And The Obtained Results Were Validated. In The Frontal Face Of The Bus Without Bumper And Crash Box, The Maximum Results Of Deformation, Stress, And Strain Are 1.26e-03 M, 1.78e+07 Pa, And 7.31e-03 J, Respectively. Whereas, With Bumper And Crash Box, The Maximum Results Of Deformation, Stress, And Strain Are 2.89e-05 M, 8.24e+05 Pa, And 4.21e-03 J, Respectively. So , Average Percentile Advantage Of Bumper Beam And Crash Box For Strain Energy Is 38.49%, Total Deformation Is 2.52%, And Alternative Stress Is 2.98%. The Maximal Percentile Advantage Of The Bumper Beam And Crash Box Is, 57.56% For Strain Energy, 2.30% For Total Deformation, And 4.63% For Von-Mises Stres. Therefore, It Is Recommended To Take Into Account The Bumper Beam And Crash Box Influence On Maximum Speed, Average Speed, And On Both Vehicle Dynamic Accidents In Order To Improve More Energy Absorption.
Keywords: Bishoftu Bus, Bumper, Crash Box, Energy Absorption, Impact Load